Is False Dilemma Really a Formal Fallacy? A Reply to Conces and Walters - Tomić, Taeda (Informal Logic, 2024)
We argue that Conces’ and Walters’ tool FM2.0 is valuable but does not show that false dilemma is a formal fallacy. The FM2.0 assumes an ambiguous use of the term ‘formal fallacy’, different from how the term is used in logic, and may show that any argument is a formal fallacy. Moreover, the FM2.0 is developed by using one type of false disjunctive syllogism. However, the adequate application of FM2.0 on false dilemma does not lead to an invalid augmented argument, contrary to what is expected in FM2.0, even assuming the ambiguous use of the term ‘formal fallacy’.